Prevalence of suicidal ideation, depression, and family dysfunction in first-year students of the Bachelor’s Degree in Medical Surgery at the Universidad Regional del Sureste - Reymundo-Sánchez, Brenda Lucila; Matías-Pérez, Diana; Mendoza-García, César Alejandro; García-Montalvo, Iván Antonio (Frontiers in Education, 2025)
Suicidal ideation is a process that is intertwined with suicidal behavior, beginning with the development of thoughts about the value of life. These thoughts can transform and trigger a chain of events ranging from planning to execute a suicide attempt. The study was conducted using a descriptive observational approach, which involved collecting numerical data and statistical analysis to determine the characteristic patterns of the investigated phenomenon. Several specific instruments were used to collect the data: the Beck Suicidal Ideation Scale, the Beck Depression Inventory, the Questionnaire for the Identification of Drug Dependence, and the Family Apgar Scale. The prevalence of suicidal ideation was 15.3%; in addition, 15.9% presented mild family dysfunction, moderate in 10.6% and severe with 21.8%; depression was recorded in mild degree with 26.5%, followed by moderate in 10.6% of the cases and severe with 7.6%. Suicidal ideation among medical students is an issue of great concern that should be addressed holistically. It is critical to create a supportive environment that promotes both the mental health and well-being of medical students.